Kesiapan Guru Dalam Pelaksanaan Kurikulum 2013 Di SD Negeri I Girimarto Kabupaten Wonogiri - Widiastuti, Ratna; , Dr. Achmad Fathoni, M.Pd (2017)
This study aims to describe: 1) teacher readiness in understanding scientific approach in SD NI Girimarto, 2) teacher readiness in implementation of scientific approach of Curriculum 2013 in SD N I Girimarto about: a) Scientific Approach Planning or Learning Implementation Plan, b) Implementation of scientific Approach In class, c) Evaluation of teachers in the implementation of scientific approach. This type of research is qualitative research. Data collection techniques used were interviews, observation, and documentation. Data analysis through data reduction measures, data presentation, conclusions and verification. The results of the research indicate that 1) The teacher's understanding of the scientific approach is known to the general teachers have understood very well about scientific approach, 2) Implementation of scientific approach in curriculum 2013 which consists of aspect, a) RPP made before implemented learning, already contained learning steps Based on scientific approach and sidah in accordance with the format of RPP Curriculum 2013, b) Implementation of saintikfik approach implemented, the teacher tried to implement the learning as planned in RPP. But there are also widely developed again. The learning activities consist of 3 main activities ie preliminary activities, core activities, and closing activities, c) Evaluation done by teacher in implementing scientific approach of curriculum 2013 using pears knowledge, attitude and skill adjusted with KI, KD and Indicator Keywords: teacher readiness, curriculum 2013, scientific approach